Development and Evaluation of pH-Responsive Pluronic F 127 Co-Poly- (Acrylic Acid) Biodegradable Nanogels for Topical Delivery of Terbinafine HCL - Shams ul Hassan; Ikrima Khalid; Liaqat Hussain; Kashif Barkat; Ikram Ullah Khan (SAGE Publishing, 2022)
Research aimed to develop and evaluate biodegradable, pH-responsive chemically cross-linked Pluronic F127 co-poly- (acrylic acid) nanogels for dermal delivery of Terbinafine HCL (TBH) to increase its permeability and as a new approach to treat skin fungal infections. TBH-loaded nanogels were successfully synthesized from acrylic acid (AA) and Pluronic F127 by free-radical copolymerization technique using N,N'-methylene bisacrylamide (MBA) as crosslinker and ammonium persulphate (APS) as initiator. Prepared nanogels exhibited 93.51% drug entrapment efficiency (DEE), 45 nm particle size, pH-dependent swelling and release behavior. Nanogels were characterized using different physicochemical techniques. The ex-vivo skin retention studies through rat skin showed about 42.34% drug retention from nanogels while 1% Lamisil cream (marketed product) showed about 26.56% drug retention. Moreover, skin irritation studies showed that nanogels were not irritating. Nanogels showed improved in-vitro antifungal activity against Candida albicans compared to commercial product. In-vivo studies on rats infected with Candida albicans confirmed superiority of nanogels over 1% Lamisil for eradication of fungal infection. This confirms that TBH loaded in Pluronic F127 co-poly-(acrylic acid) nanogels provided greater targetibility and cure rates of poorly soluble TBH in animal model and hence nanogels could be a potential carrier for effective topical delivery of TBH for skin fungal infection treatment.